2017
DOI: 10.1044/2016_jslhr-s-16-0084
|View full text |Cite
|
Sign up to set email alerts
|

Examining a New Method to Studying Velopharyngeal Structures in a Child With 22q11.2 Deletion Syndrome

Abstract: The imaging protocol described in this study presents an effective means to counteract difficulties in imaging young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…All participants completed an MRI safety screening prior to approaching the magnet. A child-friendly MRI protocol was utilized to prevent potential pitfalls associated with MRI (Kollara and Perry, 2014; Kollara et al, 2016; Kollara et al, 2017). The participants listened to the sounds of the MRI scanner by listening to audio samples of MRI noise played on an iPad and were encouraged to watch the participant being imaged before them.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants completed an MRI safety screening prior to approaching the magnet. A child-friendly MRI protocol was utilized to prevent potential pitfalls associated with MRI (Kollara and Perry, 2014; Kollara et al, 2016; Kollara et al, 2017). The participants listened to the sounds of the MRI scanner by listening to audio samples of MRI noise played on an iPad and were encouraged to watch the participant being imaged before them.…”
Section: Methodsmentioning
confidence: 99%
“…The use of a laryngeal mask airway, commonly used with sedation, distorts the oral and pharyngeal structures and can produce variations in velar measurements (Perry et al, 2011). Kollara et al (2017) published a case study examining the feasibility of a child-friendly scanning protocol on imaging a single child with 22q11.2DS, without the use of sedation. Preliminary data revealed the levator muscle to be shorter and demonstrate a U-shaped configuration.…”
Section: Introductionmentioning
confidence: 99%
“…However, even with a negative hearing history, participants with 22q11DS still demonstrated hypoplasia of the TVP. Hypoplasia of the levator muscle has also been reported in the literature as an associated feature of patients with 22q11DS (Kollara et al, 2017). Fuchs et al (2015) observed a relationship between OME and a hypoplastic levator muscle using 2 mice models of 22q11DS ( Df1/+ and Tbx1 +/− ).…”
Section: Discussionmentioning
confidence: 75%
“…22 Static imaging studies have found the levator muscle to be highly dysmorphic in the 22q11.2DS population. [8][9][10][11][12] Specifically, studies have demonstrated that the levator muscle is shorter, thinner, and descends at a more obtuse angle from the cranial base in individuals with 22q11.2DS compared to nonsyndromic groups. We had hypothesized that children with 22q11.2DS would demonstrate minimal levels of levator muscle contraction going from rest to /i/ due to levator muscle dysmorphology and reported hypoplasia.…”
Section: Differences Across Conditionsmentioning
confidence: 99%
“…Static MRI investigations so far in the 22q11.2DS population have reported variations in velopharyngeal muscles among individuals with 22q11.2DS, including a short, thin, asymmetric levator muscle with an increased angle of origin and a significantly shorter origin-to-origin distance. 1,[8][9][10][11][12] However, many of these studies utilized sedation, limiting the analysis of the velopharyngeal port at rest only. There is a continued need for imaging studies to assess both velopharyngeal structures and muscle function.…”
Section: Introductionmentioning
confidence: 99%